Assistance for crime victims: Evaluation of the pilot programme: Assistance for crime victims: Evaluation of the pilot programme (Archives of Criminology, 2025)
The programme “Assistant for crime victims”, implemented by the Crime Victims Assistance Foundation and the Blue Line, aimed to support victims by having assistants present during legal proceedings. The pilot programme entailed training volunteers in law, psychology and trauma. Surveys and interviews with assistants, victims and law enforcement conducted to evaluate the programme rated the usefulness of the training highly and demonstrated the real support provided by the assistants. The volunteers provided emotional and practical support, facilitating interactions between victims and institutions. The findings emphasize the need for further systemic support for developing and formally recognising assistants within aid structures. The importance of volunteer involvement, training quality and collaboration with public institutions was also highlighted.